Processes for non-destructive transfer of graphene: widening the bottleneck for industrial scale production. Issue 22 (14th June 2015) - Zaretski, Aliaksandr V.; Lipomi, Darren J.
<x xml:space="preserve">Abstract</x> Efficient and environmentally benign processes for production of single-layer graphene are needed to enable large-area applications.